HUBUNGAN SELFCARE DENGAN KUALITAS HIDUP PADA PASIEN DIABETES MELLITUS DI RAWAT JALAN PUSKESMAS SUKORAME KOTA KEDIRI - Nur Fahma Laili; Neni Probosiwi; Tsamrotul Ilmi; Arifani Siswidiasari; Mujtahid Bin Abd Kadir (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Diabetes mellitus is a disease that is currently an important concern. Because it is a type of disease whose number of sufferers is increasing every year. Diabetes mellitus is characterized by an increase in blood glucose levels above normal fasting > 126 mg/dl. The majority of diabetes mellitus sufferers are Type 2 where insulin sensitivity occurs so that insulin cannot be produced in sufficient quantities. The factors causing type 2 DM are a bad lifestyle. Self-care is a management action carried out by diabetes mellitus patients to maintain insulin levels and plasma sugar levels within the normal range. That so minimizing the occurrence of complications and death if the quality of life is poor. The aim of this study was to determine the relationship between self-care and quality of life in outpatients with diabetes mellitus at the Sukorame Community Health Center, Kediri City. This research uses a cross sectional design. The number of samples used a purposive sampling technique with a total sample of 93 respondents. Data collection was carried out using the Summary of Diabetes Self Care Activity (SDSCA) questionnaire and WHOQOL Questionnaire- Bref. The results of data analysis were carried out using the SPSS Chi Square Test.